2011
DOI: 10.1007/s10528-011-9468-y
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphism of the Apolipoprotein B Gene and Association with Plasma Lipid and Lipoprotein Levels in the Mongolian Buryat

Abstract: Allele frequencies at six RFLP sites (Ins/Del, ApaLI, AluI, XbaI, MspI, and EcoRI) of the apolipoprotein B gene (APOB) and the relationship of genotypes with plasma lipid and lipoprotein levels in the Mongolian Buryat were investigated. Common alleles at these sites in 110 Buryat subjects were I, G, A-, X-, M+, and E+; the frequencies of 0.809-0.991 differed strikingly from those of a few Asians and most Europeans. Five unambiguous haplotypes of all sites were revealed at 74%; haplotype… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 53 publications
1
16
1
Order By: Relevance
“…Also, Kammerer, et al among the Mexican American families has been found that homozygotes for the Del allele had significantly higher mean levels LDL-C than Ins homozygotes [29]. The results from our study disagree with Tsunoda and Cavalli, et al that exhibited no significant difference between ApoB Ins/Del polymorphism and lipid profile [30,31]. The findings of the present study indicate potential effects of the gene on dyslipidemia and obesity in patients with T2D.…”
Section: Hdl-c (X ± Sd (Mg/dl) CV (%))contrasting
confidence: 99%
“…Also, Kammerer, et al among the Mexican American families has been found that homozygotes for the Del allele had significantly higher mean levels LDL-C than Ins homozygotes [29]. The results from our study disagree with Tsunoda and Cavalli, et al that exhibited no significant difference between ApoB Ins/Del polymorphism and lipid profile [30,31]. The findings of the present study indicate potential effects of the gene on dyslipidemia and obesity in patients with T2D.…”
Section: Hdl-c (X ± Sd (Mg/dl) CV (%))contrasting
confidence: 99%
“…A higher prevalence of atherosclerotic plaques in carotid arteries of T homozygotes has also been reported (13). Some studies have also found association of this polymorphism with CVD, increased apoB, TC, TG, and LDL levels, and decreased HDL levels (5,(14)(15)(16)(17). On the other hand, some studies found no association between these parameters (9,11,18).…”
Section: Introductionmentioning
confidence: 95%
“…These include a common polymorphism (rs11279109) in the promoter region coding for the signal peptide. The deletion allele ( sp24, D ) codes for the 24-amino acid signal peptide that lacks the hydrophobic leucine-alanine-leucine residues affecting protein hydrophobicity [ 16 , 17 ], and has been shown to be associated with dyslipidemia, body mass index (BMI) and other phenotypes [ 18 22 ]. Other common polymorphisms are found in the coding sequences of exon 26, spanning 7572 bp [ 12 ] including a single nucleotide polymorphism (SNP) in the consensus sequence of the receptor-binding region [ 15 ] that can affect the binding affinity of the ligand to the LDL receptor [ 15 , 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…SNPs, including codons 3611 (rs693) and 4154 (rs1801701), result in amino acid substitution of glutamine to arginine and glutamic acid to lysine, respectively. These SNPs have been shown to be associated with variation in total cholesterol (TC) and low density lipoprotein-cholesterol (LDL-C) levels [ 20 , 22 , 24 , 25 ]. In addition, another commonly studied polymorphism is found in the APOB gene in exon 29 (rs1042031) involves a silent mutation from cytosine to thymine in the third base of codon 2488 and has been reported to be associated with dyslipidemia [ 20 , 22 , 23 , 25 ].…”
Section: Introductionmentioning
confidence: 99%